THE INFLUENCE OF BRAND IMAGE, PRICE, SERVICE QUALITY AND FACILITIES ON CUSTOMER SATISFACTION AT ASTON HOTEL MANADO - Suwandi, Monica M.; Mananeke, Lisbeth; Taroreh, Rita N. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The economic condition of a country will change the mindset of people, so what happened in Indonesia it determines the public goods and services, in accordance with ability of business players and their business oriented towards the consumer. Consumers free use of money and free compare products or services and factors associated with services like the brand image, price, service quality and facilities. These days, service business in this case of hotel, have a thighter competition. As the new competitor shows up in the same aspect. The purpose of this research to know the influence of the brand image, price, service quality and facilities towards satisfaction of consumers either simultaneously and partialy. The type of research used is associative research. The sample used is 96 respondents. The analysis instrument used Multiple Linear Regression , to test the hypothesis of the use of the f test and test t. The results of influence shows simultaneously brand image, price, service quality, facility have significant to the cunsomer satisfactionÂ  while facilities do not have affect significant influence on consumer satisfaction. Management Aston Hotel should pay more attention to the brand image, price and quality of services to improve customer satisfaction. Keywords: brand image, price, service quality, facilities, customer satisfaction